The past and future city : how historic preservation is reviving America's communities - Meeks, Stephanie; Murphy, Kevin C., 1974- (2016)
"In The Past and Future City, Stephanie Meeks, the president of the National Trust for Historic Preservation, describes in detail, and with unique empirical research, the many ways that saving and restoring historic fabric can help a city create thriving neighborhoods, good jobs, and a vibrant economy. She explains the critical importance of preservation for all our communities, the ways the historic preservation field has evolved to embrace the challenges of the twenty-first century, and the innovative work being done in the preservation space now"--Provided by publisher.
Introduction: The Powers of Place -- Downtown Is For People: Competing Visions of the Ideal American City -- Older, Smaller, Better: How Older Buildings Enhance Urban Vitality -- Making It Work for Your City: Unleashing the Power and Potential of Historic Fabric -- Buildings Reborn: Keeping Historic Properties in Active Use -- Our Diverse History: Towards More Inclusive History and Communities -- Mitigating the Great Inversion: The Problems of Affordability and Displacement -- The Greenest Buildings: Preservation, Climate Change, and the Environment -- Conclusion: The Future of the Past: Livable Cities and the Future of Preservation.
Includes bibliographical references (pages 313-320) and index.
Keywords: City planning -- Social aspects -- United States; Historic preservation -- United States; Cultural property -- Protection -- United States; Historic buildings -- Conservation and restoration -- United States; ARCHITECTURE -- Historic Preservation; ARCHITECTURE -- Sustainability & Green Design; ARCHITECTURE -- Urban & Land Use Planning; City planning -- Social aspects; Cultural property -- Protection; Historic buildings -- Conservation and restoration; Historic preservation; United States